Seasonal dynamics and spatial distribution of Dactylogyrus cruciferWagener, 1857 on the gills of roach (Rutilus rutilus L.) from Lake Sapanca, Turkey - (:unkn) unknown (My University, 2010)
Bu çalışmada, Sapanca Gölünde Rutilus rutilus’un solungaçlarındaki monogenean parazit Dactylogyrus crucifer’in mevsimsel dinamikleri ve mekansal dağılımı belirlendi. 2005 yılı Ocak ve Kasım ayları arasında toplam 183 kızılgöz balığı ile aylık olarak çalışılarak parazitin en yüksek ortalama yoğunluğu Mart’ta (227.1 ± 87.14) ve en düşük değeri Kasım’da (13.3 ± 8.2) bulundu. Bu nedenle 2006 yılı Mart ayında D. crucifer’in mekansal dağılımı araştırıldı. Mekansal dağılım yönünden hiçbir anlamlı fark bulunamadı.

This study determined the seasonal dynamics and spatial distribution of the monogenean parasite Dactylogyrus crucifer on the gills of roach Rutilus rutilus from Lake Sapanca, Turkey. A total of 183 specimens of roach between January and November 2005 were examined in monthly intervals. The highest mean intensity was recorded in March (227.1 ± 87.14) and the lowest in November (13.3 ± 8.2). Fifty three R. rutilus specimens were therefore investigated for spatial distribution of D. crucifer in March 2006. No significant differences in distribution were found according to any of the spatial determinants.
Sapanca Gölü (Türkiye)’nde Kızılgöz Balığı (Rutilus rutilus L.)’nın solungaçlarında Dactylogyrus cruciferWagener, 1857 in mevsimsel dinamikleri ve mekansal dağılımı
Keywords: Biyoloji